Pentingnya memahami konsep diri remaja sebagai identitas budaya dalam mengeksplorasi perilaku masyarakat - Kushendar, Kushendar; Hernisawati, Hernisawati; Abdi, Sofyan (Pusat Kajian Bimbingan dan Konseling FIPPS Unindra, 2018)
The concept of self is an important part of a person's cultural identity in behaving in society. The concept of self as a cultural identity covers a person's specific things about the views, judgments and cultural beliefs owned. For teens, having a positive self-concept is a must-have, especially as a cultural identity that is owned and proud of. The concept of adolescent self as cultural identity is the main step to determine who I am ?, what should I do ?, and what should I be ?, such questions are a problem that generally occurs in every teenager, by understanding positive cultural identity, it is expected that adolescents can determine good social behavior in the community.